Peran Kegiatan Ekstrakurikuler dalam Upaya Meningkatkan Prestasi Belajar Siswa di SMP Muhammadiyah 3 Medan - Fahri Richki; Bahtiar Siregar; Halimatusaa’diah Halimatusaa’diah; Maya Santika; Maulidza Nabila; Nurlaila Hayati Ritonga (Departement of Mathematics Education, 2024)
The role of extracurricular activities in coaching and developing students at school is very important in providing a holistic and in-depth learning experience outside the regular academic environment. The aim of this research is to find out how extracurricular activities are implemented at SMP Muhammadiyah 3 Medan and the role of extracurriculars in improving student learning achievement at SMP Muhammadiyah 3. The research method used in this research is using the literature study method or what can be called library research by examining journals and book. The research instruments used in this research were observation and interviews. Based on the research results, it was found that learning at SMP Muhammadiyah 3 Medan was carried out over 6 working days. Where every Saturday is filled with extracurricular activities. The types and forms of extracurricular activities carried out at SMP Muhammadiyah 3 Medan include dance, theater, drumband, paskib, football and futsal, English, Science and Tahfidz. Apart from that, there are also extracurricular activities such as choir and dancing. Extracurriculars in Improving Student Learning Achievement at SMP Muhammadiyah 3 Medan help complete students' education holistically. Apart from focusing on academic aspects, extracurricular activities help develop students' physical, social, emotional and intellectual aspects, and create an important balance in their development. Participants who play an active role in extracurricular activities can also hone skills that they do not get in academic learning. Skills that can be honed through extracurricular activities include communication skills, leadership, cooperation, creativity and discipline